The Origin of Black Smock and White Collar - (:unkn) unknown (EDAM, 2009)
Although there are many empirical studies on the functions of school uniform, studies which focus on the origins of school uniform are neglected. Purpose of this study is to reveal historical origins of black smock and white collar. To achieve this purpose, a qualitative research method was adopted. As a result of the research, it was determined that the origins of black smock and white collar lie in the university and charity school uniforms in England. In France and England, school uniforms have mostly been affected by the religious tradition. Western educational system was a model for Turkey. Notre Dame de Sion and Saint Joseph which were founded in the middle of the nineteenth century in Istanbul were probably the first models of black smock and white collar in Turkey.
Keywords: School Uniform; School Clothes; White Collar; Smock; Black Smock; SCHOOL UNIFORMS